PENAMBAHAN SARI JERUK NIPIS (Citrus aurantifolia) TERHADAP MUTU SIRUP BUAH KUNDUR (Benincasahispida) - Fikri ' Hamidi; Raswen ' Efendi; Faizah ' Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to obtain the best ratio of bligo extracts and lime extracts in the manufacturing of syrup. This research used Complete Randomized Design (CRD) with four treatments and four replication which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research included KD0 (ratio of bligo extracts and lime extracts 100 : 0), KD1 (bligo extracts and lime extracts 95 : 5), KD2 (ratio bligo extracts and lime extracts 90 : 10), KD3 (bligo extracts and lime extracts 85 : 15). The result showed that the ratio of bligo extracts and lime extracts significantly affected pH, sucrose, viscosity, total dissolved and sensory value (colour, flavour , taste and overall acceptability) but are did not significant affected the sensory value viscosity. The best treatment was KD3 (bligo extracts and lime extracts 85 : 15) with pH 3,96, sucrose 65%, viscosity 295,82cP, total dissolved 70,63 obrix and sensory scores of  KD3 are 2,47 (colour), 2,37 (flavour), 1,87 (taste), and comprehersive score (3,80).   Keywords: Syrup, bligo and lime.